Global Investments and Regional Development Trajectories: the Missing Links - Riccardo Crescenzi; Simona Iammarino (London School of Economics and Political Science (LSE), European Institute, 2016)
Regional economic development has been long conceptualised as a non-linear, interactive and socially embedded process: these features were traditionally regarded as spatially mediated and highly localised. However, unprecedentedly fast technological change coupled with the intensification of global economic integration processes has spurred the need to place regional development in a truly open and interdependent framework. Despite substantial progress made by the academic literature, rethinking regional development in this perspective still presents a number of challenges in terms of concepts, empirical evidence and policy approaches. Following an interdisciplinary assessment of how openness and connectivity – proxied by one particular of the many cross-border flows, i.e. global investments – interact with regional economic development trajectories, this paper presents a picture of the geography of foreign investments from and to the European regions and its change after the financial and economic crisis in 2008. This simple exercise allows us to shed some initial light on how the operationalisation of regional connectivity can improve our empirical understanding of the evolution of regional economies and the policy approach needed to support their reaction to change.
Keywords: F2; R11; R12; O19; O3; O52; 330; FDI; regions; local-global connectivity; regional development; Europe